THE CORRELATION BETWEEN PERCEPTUAL LEARNING STYLES AND READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF MTsN 1 KEDIRI - winoto, Setiyo aji (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 2 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research is aimed to know whether there is significant and simultaneously correlation between perceptual learning styles and reading comprehension of the second year students of MTsN 1 Kediri. The approach used is descriptive quantitative. The sample is 166 students. The instrument used was questionnaires and test. The result was there is no significant and simultaneously correlation among simultaneously correlation between perceptual learning styles and reading comprehension of the second year students of MTsN 1 Kediri. The value of correlation between X1, X2, X3 and Y is 0.004, then for the level of significance p value 0.875 greate than 0.05. It is recommended that perceptual learning styles was not the factors affecting thier reading comprehension.